Crustal Thinning From Orogen to Back‐Arc Basin: The Structure of the Pannonian Basin Region Revealed by P‐to‐S Converted Seismic Waves. Issue 7 (12th July 2021) - Kalmár, Dániel; Hetényi, György; Balázs, Attila; Bondár, István
Abstract: We present the results of P ‐to‐ S receiver function analysis to improve the 3D image of the sedimentary layer, the upper crust, and lower crust in the Pannonian Basin area. The Pannonian Basin hosts deep sedimentary depocentres superimposed on a complex basement structure and it is surrounded by mountain belts. We processed waveforms from 221 three‐component broadband seismological stations. As a result of the dense station coverage, we were able to achieve so far unprecedented spatial resolution in determining the velocity structure of the crust. We applied a three‐fold quality control process; the first two being applied to the observed waveforms and the third to the calculated radial receiver functions. This work is the first comprehensive receiver function study of the entire region. To prepare the inversions, we performed station‐wise H ‐Vp/Vs grid search, as well as Common Conversion Point migration. Our main focus was then the S ‐wave velocity structure of the area, which we determined by the Neighborhood Algorithm inversion method at each station, where data were sub‐divided into back‐azimuthal bundles based on similar Ps delay times. The 1D, nonlinear inversions provided the depth of the discontinuities, shear‐wave velocities and Vp/Vs ratios of each layer per bundle, and we calculated uncertainty values for each of these parameters. We then developed a 3D interpolation method based on natural neighbor interpolation to obtain the 3D crustal structure from the local inversion results. We present the sedimentary thickness map, the first Conrad depth map and an improved, detailed Moho map, as well as the first upper and lower crustal thickness maps obtained from receiver function analysis. The velocity jump across the Conrad discontinuity is estimated at less than 0.2 km/s over most of the investigated area. We also compare the new Moho map from our approach to simple grid search results and prior knowledge from other techniques. Our Moho depth map presents local variations in the investigated area: the crust‐mantle boundary is at 20–26 km beneath the sedimentary basins, while it is situated deeper below the Apuseni Mountains, Transdanubian and North Hungarian Ranges (28–33 km), and it is the deepest beneath the Eastern Alps and the Southern Carpathians (40–45 km). These values reflect well the Neogene evolution of the region, such as crustal thinning of the Pannonian Basin and orogenic thickening in the neighboring mountain belts. Plain Language Summary: I performed the first comprehensive P ‐to‐ S receiver function analysis in the wider region of the Pannonian Basin using the most recent data set available. My study is based on a relatively long time‐span of seismological dataset (2002–2019) of digital broadband waveforms with uniform automatic waveform processing and thorough quality control procedures. I performed preliminary calculations of the Moho depth and average Vp/Vs ratio of the crust using the H ‐Vp/Vs grid search scheme and Common Conversion Point migration method. The main focus was the nonlinear inversion of the receiver functions at each station. In order to take into account possible topography in the major discontinuities, I grouped the receiver functions at the stations according to their back azimuth. The receiver functions obtained from a network of closely spaced stations allowed us to infer a 3D structural and shear‐wave velocity model of the region. I have developed a new interpolation and imaging algorithm. I mapped the thickness of major intracrustal layers and determined their S ‐wave velocity conditions and Vp/Vs ratios of these. The Conrad depth, upper crust, and lower crust thickness maps are the first for the Pannonian Basin region. The Moho depth map presents local variations with more finely and better resolved values than previous investigations. Key Points: First comprehensive receiver function study of the Pannonian Basin and neighboring areas from the hitherto densest network S ‐wave velocity inversion and a novel 3D interpolation scheme Geodynamic description of the Pannonian Basin in the upper and lower crust